Men at risk: correlates of verbal, physical and sexual violence against men who have sex with men across selected cities in India - Suraj Pal; Praveen Kumar Pathak; Margubur Rahaman; Niharika Tripathi (BMC, 2024)
Abstract Background Five distinct forms of violence - Physical, Verbal, Sexual, Cyber, and Relational - persistently afflict sexual minorities worldwide. The presence of feminine attributes in Men who have Sex with Men is inherently linked to a heightened susceptibility to various manifestations of violence, thereby exerting detrimental repercussions on both the physical and mental well-being of these individuals. This correlation stands as a principal contributor to the alarmingly elevated rates of suicide attempts among Men who have Sex with Men, particularly during their early years. Data and Methods This cross-sectional study investigates the risk factors for violence against Men who have Sex with Men in six metropolitan cities across India. Quantitative data were gathered from 300 self-identified Men who have Sex with Men, with 240 providing only quantitative data, while both quantitative and qualitative data were collected from a subset of 60 respondents, ranging in age from 18 to 70 years. Quantitative analysis was conducted using descriptive statistics, chi-square tests, and binary logistic regression to explore the likelihood of different types of violence. Qualitative data collected through in-depth interviews, were analyzed thematically to provide contextual depth and validate the quantitative findings, focusing on specific incidents and key themes associated with violence among Men who have Sex with Men. Results More than 60 per cent of the respondents encountered at least one type of violence due to their sexuality. More than half of the respondents who engaged in the receptive role during sexual activity reported experiencing sexual violence. The likelihood of encountering verbal violence was found to be nearly six times higher among respondents who were receptive than penetrative sexual partners. Respondents of Muslim religion exhibited a 2.6-fold increase in the likelihood of experiencing sexual violence compared to their Hindu counterparts. Conclusion Violence against Men who have Sex with Men is a pervasive issue in the six metropolitan cities studied in India, particularly affecting individuals with lower education and low income. These findings resonate with global research, which identifies similar risk factors for violence against sexual minorities, especially in regions with deep-rooted homophobia and socio-economic inequalities. Insights from this study underscore the urgent need for targeted policies and interventions to create a safer, more inclusive environment for this population in India and other parts of the Global South.